Polyaniline coated sulfonated TiO2 nanoparticles for effective application in proton conductive polymer membrane fuel cell. (March 2019) - Elakkiya, S.; Arthanareeswaran, G.; Ismail, A.F.; Das, Diganta B.; Suganya, R.
Graphical abstract: Highlights: TiO2 was surface modified by sulfonation and coating of PANI in sulfonated TiO2 . Surface modified TiO2 enhanced ion exchange capacity of composite membrane. STiO2 –PANI composite membranes exhibited excellent proton conductivity than the pristine SPES membrane. Abstract: The sulfonated polyethersulfone (SPES) with modified TiO2 proton exchange membrane performance for the fuel cell application was reported. TiO2 nanoparticles investigated for the fuel cell performance were modified by sulfonation and surface coated using polyaniline (PANI). Fabricated membranes were analyzed in terms of water uptake, swelling ratio, methanol uptake, ion exchange capacity, chemical stability and thermal properties. Surface and structural properties of the membranes were characterized by Field Emission Scanning electron microscope (FESEM). To understand the interaction between polymer and nanoparticle, Fourier transform infrared (FTIR) and X-ray diffraction (XRD) characterization for the membranes were performed. Highest proton conductivity is 2.30 × 10 −4 S/cm with SPES/STiO2 –PANI (0.5%) composite membrane. The presence of modified TiO2 with amine group of PANI and sulfonic acid group were the main factors for the highest conductivity value. The composite membrane with modified TiO2 shows excellent chemical stability and thermal properties. Thus, the composite membrane incorporated with STiO2 –PANI is a promising proton conducting material for fuel cell application.